Control de ingresos y egresos en el Gobierno Autónomo Descentralizado (GAD) Municipal del Cantón Puebloviejo en el periodo 2022-2023. - Alarcón Rosado, Juleidy María (2024)
The control of income and expenses in the Municipal Autonomous Decentralized Government (GAD) of the Puebloviejo Canton during the period 2022-2023 is crucial to guarantee adequate financial management and transparency in the use of public resources, this process involves detailed supervision of all sources of revenue, such as local taxes, State transfers and other financial resources, as well as rigorous monitoring of municipal expenditures on programs, public services and infrastructure projects. During this period, the Municipal GAD of Puebloviejo faces the challenge of maximizing available income while efficiently managing expenditures to meet the needs of the local community, this requires implementing robust accounting and budgeting systems and procedures that ensure the correct allocation and use of public funds, minimizing risks of embezzlement or improper use. Budget planning plays a fundamental role, allowing the GAD to prioritize investments in critical areas such as education, health, road infrastructure and basic services, likewise, the periodic evaluation of financial results and compliance with budgetary goals are essential to adjust strategies and ensure long-term fiscal sustainability. Clarity when rendering accounts is fundamental in the process, guaranteeing the community to have free access to information in a precise and clear way but above all that it is understandable to identify how equitable administration of the public resources of the community is achieved. entity, this practice strengthens the trust of people in the sector towards local institutions, promoting continuous improvement.